Acceptor plane expansion enhances horizontal orientation of thermally activated delayed fluorescence emitters - Xiang, Yepeng (Sci Adv, 2020)
Manipulating orientation of organic emitters remains a formidable challenge in organic light-emitting diodes (OLEDs). Here, expansion of the acceptor plane of thermally activated delayed fluorescence (TADF) emitters was demonstrated to selectively modulate emitting dipole orientation. Two proof-of-the-concept molecules, PXZPyPM and PXZTAZPM, were prepared by introducing a planar 2-phenylpyridine or 2,4,6-triphenyl-1,3,5-triazine substituent into a prototypical molecule (PXZPM) bearing a pyrimidine core and two phenoxazine donors. This design approach suppressed the influence of substituents on electronic structures and associated optoelectronic properties. Accordingly, PXZPyPM and PXZTAZPM preserved almost the same excited states and similar emission characteristics as PXZPM. The expanded acceptor plane of PXZPyPM and PXZTAZPM resulted in a 15 to 18% increase in horizontal ratios of emitting dipole orientation. PXZPyPM supported its green device exhibiting an external quantum efficiency of 33.9% and a power efficiency of 118.9 lumen per watt, competitive with the most efficient green TADF OLEDs reported so far.